2023
DOI: 10.3390/ijms241310957
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Fingerprints of Effective Fluoxetine Treatment in the Prefrontal Cortex of Chronically Socially Isolated Rats: Marker Candidates and Predictive Metabolites

Abstract: The increasing prevalence of depression requires more effective therapy and the understanding of antidepressants’ mode of action. We carried out untargeted metabolomics of the prefrontal cortex of rats exposed to chronic social isolation (CSIS), a rat model of depression, and/or fluoxetine treatment using liquid chromatography–high resolution mass spectrometry. The behavioral phenotype was assessed by the forced swim test. To analyze the metabolomics data, we employed univariate and multivariate analysis and b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 83 publications
0
1
0
Order By: Relevance
“…In support of this, downregulated Impa1, responsible for the production of inositol and essential for the synthesis of phosphatidylinositol, was found. Moreover, a recent metabolomic study demonstrated increased levels of the components of phosphatidylinositol, such as myo-inositol, following CSIS (referred to as CSIS-susceptible rats) in the PFC as one of the most interesting variables for stratifying CSIS-susceptible vs. control rats [ 33 ]. Downregulated proteins involved in the Ras subfamily of GTPases, such as Rap1b, Rab1A, Rab2a, and Rab1b, were identified as predictive proteins using ML algorithms.…”
Section: Discussionmentioning
confidence: 99%
“…In support of this, downregulated Impa1, responsible for the production of inositol and essential for the synthesis of phosphatidylinositol, was found. Moreover, a recent metabolomic study demonstrated increased levels of the components of phosphatidylinositol, such as myo-inositol, following CSIS (referred to as CSIS-susceptible rats) in the PFC as one of the most interesting variables for stratifying CSIS-susceptible vs. control rats [ 33 ]. Downregulated proteins involved in the Ras subfamily of GTPases, such as Rap1b, Rab1A, Rab2a, and Rab1b, were identified as predictive proteins using ML algorithms.…”
Section: Discussionmentioning
confidence: 99%